Sleeping Patterns in Patients with Opioid Use Disorder: Effects of Opioid Maintenance Treatment and Detoxification. Issue 3 (26th May 2020) - Chrobok, Agnieszka I.; Krause, Daniela; Winter, Catja; Plörer, Diana; Martin, Gabriele; Koller, Gabriele; Adorjan, Kristina; Canolli, Minavere; Adam, Roland; Wagner, Elias M.; Peles, Einat; Paul, Dietmar; et al.
ABSTRACT: The aim of the study was to explore whether abstinent patients on recent opioid detoxification or on opioid maintenance treatment suffer from sleeping problems. 199 patients on opioid maintenance treatment (methadone, diacetylmorphine and buprenorphine) or recent opioid detoxification were included in this exploratory cross-sectional study. We used the Pittsburgh Sleep Quality Index (PSQI) and the Regensburger Insomnia Scale (RIS) in order to assess potential sleeping problems. There was a significant effect of the condition "opioid maintenance" or "recent opioid detoxification" on the total score of PSQI and RIS. All opioid maintenance drugs used by the study population were associated with more sleeping problems compared to the detoxification group when calculated with RIS values. Recently abstinent patients (opioid detoxification) displayed significantly fewer sleep disturbances than opioid-maintained patients. Since sleeping problems can seriously impair treatment success and quality of life, screening for sleep disturbances and their subsequent treatment is of pronounced relevance.